Analysis of the adequacy of labeling of protein-based supplements (Research, Society and Development, 2019)
The present study had as objective to analyze the conformity with the current legislation of the labels of protein supplements marketed in a municipality of Maranhão. The analysis was performed with protein dietary supplements, the sale in specialized stores and drugstores marketed in said municipality. The labels were analyzed according to the legislation in force for physical activity practitioners, RDC nº18 / 2010, according to parameters presented by ANVISA. Fifty-one labels of supplements produced by sixteen manufacturers were analyzed. It was observed that 90.2% of the samples presented some item in disagreement with the legislation. Among the irregularities mentioned are the non-presentation of the product registration number (70.6%), non-nutritional and non-nutrient fibers (37.3%), product designation 1/3 the size of source of the brand (23.5%), minimum 10g of proteins in the portion (23.5%), 50% of the VET from proteins (17.6%), among others. The results highlight the need for continuous and rigorous monitoring of protein supplementation labels, in order to guarantee the proper orientation of the consumer in the purchase of products.